Seeing the City Digitally Processing Urban Space and Time - Rose, Gillian (Cities and Cultures, 2022)
This book explores what's happening to ways of seeing urban spaces in the contemporary moment, when so many of the technologies through which cities are visualised are digital. Cities have always been pictured, in many media and for many different purposes. This edited collection explores how that picturing is changing in an era of digital visual culture. Analogue visual technologies like film cameras were understood as creating some sort of a trace of the real city. Digital visual technologies, in contrast, harvest and process digital data to create images that are constantly refreshed, modified and circulated. Each of the chapters in this volume examines a different example of this processual visuality is reconfiguring the spatial and temporal organisation of urban life.